2003
DOI: 10.1179/000349803235002380
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing mebendazole and secnidazole for the treatment of giardiasis

Abstract: To compare the efficacy of the two drugs in the treatment of giardiasis, 146 children (aged 5-15 years) with confirmed Giardia lamblia infection were randomly allotted to treatment with mebendazole (200 mg three times daily for 3 days) or secnidazole (30 mg/kg, in a single dose). Parasitological response to treatment was evaluated in each child by the microscopical examination of faecal samples collected 3, 5 and 7 days after he or she had completed treatment. Although the frequency of cure was higher for secn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 24 publications
2
26
0
4
Order By: Relevance
“…It has been reported that secnidazole in a single dose is effective in eradication of giardiasis. [13][14][15] In previous studies, we showed significant parasitologic and clinical cure in children infected with G. intestinalis 3 and increased mean hemoglobin levels after treatment with secnidazole. 16 In addition, detection of specific protein bands and serum antibody responses against Giardia species proteins by Western blotting and ELISA has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that secnidazole in a single dose is effective in eradication of giardiasis. [13][14][15] In previous studies, we showed significant parasitologic and clinical cure in children infected with G. intestinalis 3 and increased mean hemoglobin levels after treatment with secnidazole. 16 In addition, detection of specific protein bands and serum antibody responses against Giardia species proteins by Western blotting and ELISA has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…El tratamiento tradicional contra la giardiasis en seres humanos incluye el uso de 5-nitroimidazoles como metronidazol, tinidazol y ornidazol, que a pesar de ser una terapia efectiva en poblaciones con prevalencias altas, puede consistir del uso de una dosis oral única del medicamento que posee una baja toxicidad y relativamente pocos efectos secundarios (15), por ejemplo podría ser proporcionada mediante secnidazol (15)(16)(17). Al igual que en los exámenes entre seres humanos, se obtuvo una tasa de erradicación parasitológica del 100% después del tratamiento con una dosis única de secnidazol en gatos infectados con G. duodenalis (18).…”
Section: G I a R D I A D U O D E N A L I S ( G L A M B L I A A N D unclassified
“…The latter procedure was repeated for 2 times from different samples belonging to each lamb collected on day 0 by a single blinded researcher. An involvement criterion was mono infection with G. duodenalis, proved by microscopical fecal samples as reported previously (21).…”
Section: Methodsmentioning
confidence: 99%